2 Answers | Add Yours
At the start 'she' has x cars and 'he' has x cars.
If 'she' has x cars then she has x-72 cars when she gives them to 'him'.
Now 'he' has three times as many cars as 'she', so he has 3(x-72) cars.
But since they both had x cars to begin with, this must be equal to x+72 after 'she' has given him 72 cars.
So now we have an equation
2x=216+72 subtract x from both sides, and add 216 to both sides
2x=288 divide both sides by two
x=144 So they started out with 144 cars
So they both had 144 cars this means they started out with 288 cars.
Let the two kids be A & B
Both had equal number of cars so we assume that
A=x cars & B=x cars
after A gives cars to B
A=x-72 & B=x+72
It is given that B had three times as many cars as A
=> 3*(x-72) = x+72
=> 3x-216 = x+72
=> 3x-x = 72+216
=> 2x= 288
=> x= 144
Therefore in all they had 144+144 cars= 288 cars
We’ve answered 319,202 questions. We can answer yours, too.Ask a question